2013
DOI: 10.1016/j.jash.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence and stroke/TIA risk in treated hypertensives: Results from the REGARDS study

Abstract: Background The extent to which low medication adherence in hypertensive individuals contributes to disparities in stroke and transient ischemic attack (TIA) risk is poorly understood. Methods Investigators examined the relationship between self-reported medication adherence and blood pressure (BP) control (<140/90 mm Hg), Framingham Stroke Risk Score, and physician-adjudicated stroke/TIA incidence in treated hypertensive subjects (n = 15,071; 51% black; 57% in Stroke Belt) over 4.9 years in the national popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…Our study is similar to a systematic review of risk factors for intracerebral hemorrhage in the general population that found male sex and hypertension (Ariesen, Claus, Rinkel, & Algra, 2003). Our results are consistent with the previous study showing that medication nonadherence was associated with insufficient blood pressure control and increased risk of incident stroke (Cummings et al, 2013;Hussain, Azad, et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Our study is similar to a systematic review of risk factors for intracerebral hemorrhage in the general population that found male sex and hypertension (Ariesen, Claus, Rinkel, & Algra, 2003). Our results are consistent with the previous study showing that medication nonadherence was associated with insufficient blood pressure control and increased risk of incident stroke (Cummings et al, 2013;Hussain, Azad, et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The available data on stroke patients suggest that medication persistence is often sub-optimal, and that many patients are consequently at a significantly increased risk of a further stroke [6,13,16]. Although early initiation of prevention strategies has shown sustained persistence and good outcomes in some stroke patients, other evidence suggests that use of these secondary prevention therapies may not persist long-term [19].…”
Section: Journal Of Neurology and Neuroscience Issn 2171-6625mentioning
confidence: 99%
“…to take prevention medications, there is limited information on medication persistence and the impact on readmission in this population [12,15,16]. We developed a quality improvement program (Transition Coaching for Stroke or TRACS) for patients going home after stroke in order to understand the reasons for readmission.…”
Section: Introductionmentioning
confidence: 99%
“…Although effective pharmaceutical treatments are readily available and reduce the risk for major cardiovascular diseases,4 inadequate adherence among patients to hypertension medication and the inertia of physicians to intensify treatment contribute to substantial morbidity, mortality, hospitalization, and health care costs 5, 6, 7. Recent studies suggest that treatment intensification improves hypertension management even with suboptimal adherence and reduces risks of cardiovascular events and deaths 8, 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%